Predictors of hospitalization and severe disease due to breakthrough SARS‐CoV‐2 infection in fully vaccinated individuals. Issue 4 (29th July 2022) - Johnson, Steven; Mielke, Nicholas; Mathew, Trini; Maine, Gabriel N; Chen, Nai‐Wei; Bahl, Amit
Abstract: Objective: We aimed to identify risk factors for hospital admission and severe disease among fully vaccinated (FV) individuals with COVID‐19. Further, we investigated if risk factors for hospitalization and severe disease are similar between unvaccinated (UV) and vaccinated individuals. Methods: This was a multicenter, observational cohort analysis from a large regional healthcare system in metro Detroit using electronic health record data to evaluate risk factors for hospitalization and severe COVID‐19 disease. Vaccination data were retrieved using electronic medical records linked to our statewide immunization database. Consecutive adult FV and UV patients with a primary admission diagnosis of COVID‐19 were included in the comparative analysis. Partially vaccinated patients and patients who had received a booster dose were excluded. The primary outcome of this study was hospital admission and severe disease inclusive of intensive care unit (ICU) admission, mechanical ventilation, or death. Results: Between December 15, 2020 and December 19, 2021, 20, 584 emergency department visits met our inclusion criteria. Among these, 2005 (9.7%) visits consisted of FV individuals, 18, 579 (90.3%) were UV, and 40.3% of UV and 52.7% of FV required hospitalization with similar (12.7% and 12.6%, respectively) rates of severe disease. Hospitalized UV patients with severe disease were younger than their FV counterparts (49.5% <65 years vs. 13.5% p < 0.001). Risk factors for severe disease on UV and FV included age ≥65 years (UV: adjusted odds ratio [aOR] 1.49, 95% confidence interval [CI] 1.28–1.73, p < 0.001 and FV: aOR 2.50, 95% CI 1.44–4.36 p = 0.001) and weighted Elixhauser score >10 (UV: aOR 9.11, 95% CI 6.92–12.00, p < 0.001 and FV: aOR 6.04, 95% CI 2.68–13.26, p < 0.001). However, only on UV status, body mass index (BMI) ≥30 kg/m 2 was associated with increased odds of severe disease (aOR 2.59, 95% CI 2.09–3.22, p < 0.001). Conclusions: FV patients with breakthrough SARS‐CoV‐2 infection who require hospitalization and have severe disease are older and have more medical comorbidities compared to UV patients. When comparing risk factors for severe disease between UV and FV individuals, FV status is particularly associated with reduced risk among patients with a BMI ≥30 kg/m 2 and a moderate number of medical comorbidities, regardless of age, highlighting the importance of vaccination in these particularly vulnerable groups.